Clinical outcomes of kidney transplantation in older end‐stage renal disease patients: A nationwide cohort study. Issue 5 (20th February 2019) - Ko, Eun Jeong; Yang, Jaeseok; Ahn, Curie; Kim, Myoung Soo; Han, Duck Jong; Kim, Sung Joo; Yang, Chul Woo; Chung, Byung Ha; ,
Abstract : Aim: The aim of the present study was to investigate the clinical outcomes of kidney transplantation (KT) in elderly recipients compared with those in young recipients. Methods: We compared the incidence of biopsy‐proven acute rejection, death‐censored allograft survival and all‐cause mortality, and also compared the impact of high sensitization or desensitization on the clinical outcomes of elderly and young recipients. Results: A total of 4966 KT recipients from the Korean Organ Transplantation Registry were included. The definition of elderly recipients was based on age >60 years ( n  = 356), and recipients aged <60 years were defined as young recipients ( n  = 4610). The incidence of biopsy‐proven acute rejection did not differ between the two groups irrespective of the donor type; however, the impact of high sensitization was significant only in young recipients. Being an elderly recipient was an independent risk factor for death‐censored allograft failure in terms of overall and living donor KT, but not with deceased donor KT. In regard to patient death, being an elderly recipient was a significant predictor in general and in the two subgroups, and desensitization showed a significant interaction with death in the elderly recipients in the living donor KT group. Conclusions: In conclusion, KT in elderly recipients might be associated with poor allograft or patient survival in general, and especially, desensitization therapy carried out in these patients might increase the risk of patient mortality.Geriatr Gerontol Int 2019; 19: 392–398 .